2022
DOI: 10.3762/bjnano.13.26
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial nanoarchitectonics for ZIF-8 membranes with enhanced gas separation

Abstract: Metal-organic framework (MOF) membranes are potentially useful in gas separation applications. Conventional methods of MOF membrane preparation require multiple steps and high-pressure conditions. In this study, a reliable one-step interfacial synthesis method under atmospheric pressure has been developed to prepare zeolitic imidazolate framework-8 (ZIF-8) membranes supported on porous α-Al2O3 disks. To obtain optimal ZIF-8 membranes, three reaction parameters were investigated, namely, reaction temperature, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Therefore, when building materials from nanoscale units, these uncertainties are included to harmonize the various effects [55,56]. Recent publications advocating nanoarchitectonics show that it is widely applied in academic fields such as materials synthesis [57][58][59], structural control [60][61][62][63], physical phenomena [64][65][66], and basic biochemistry [67][68][69], as well as in applied fields such as catalysis [70][71][72], sensors [73][74][75], devices [76][77][78], energy [79][80][81], environment [82][83][84][85], and medicine [86][87][88][89]. Since all the materials are composed of atoms and molecules, nanoarchitectonics is considered a universal unified concept that can be applied to all targets.…”
Section: Review Introductionmentioning
confidence: 99%
“…Therefore, when building materials from nanoscale units, these uncertainties are included to harmonize the various effects [55,56]. Recent publications advocating nanoarchitectonics show that it is widely applied in academic fields such as materials synthesis [57][58][59], structural control [60][61][62][63], physical phenomena [64][65][66], and basic biochemistry [67][68][69], as well as in applied fields such as catalysis [70][71][72], sensors [73][74][75], devices [76][77][78], energy [79][80][81], environment [82][83][84][85], and medicine [86][87][88][89]. Since all the materials are composed of atoms and molecules, nanoarchitectonics is considered a universal unified concept that can be applied to all targets.…”
Section: Review Introductionmentioning
confidence: 99%
“…Yan et al [ 22 ] synthesized a UiO–66 membrane through tertiary growth at room temperature, which exhibited an optimal selectivity of 37.8 for CO 2 /N 2 . Chen et al [ 23 ] fabricated a ZIF–8 membrane under different reaction conditions, and found that the optimal temperature for synthesis of ZIF–8 membrane is 80 °C. Further, they also found that the separation factor of CO 2 /N 2 was 5.49 and the permeance of CO 2 was 0.47 × 10 –7 mol·m –2 ·s –1 ·Pa –1 under optimal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [22] synthesized a UiO-66 membrane through tertiary growth at room temperature, which exhibited an optimal selectivity of 37.8 for CO 2 /N 2 . Chen et al [23] fabricated a ZIF-8 membrane under different reaction conditions, and found that the optimal temperature for synthesis of ZIF-8 membrane is 80 • C. Further, they also found that the separation factor of CO 2 /N 2 was 5.49 and the permeance of CO 2 was 0.47 × 10 -7 mol•m -2 •s -1 •Pa -1 under optimal conditions. However, with the increasing number of MOFs synthesized by experiments and built by computer technology, it is not practical to select potential MOFMs only through experiments due to the high costs and long time periods involved.…”
Section: Introductionmentioning
confidence: 99%
“…By selecting only papers that include the word “nanoarchitectonics” in the title, one would appreciate that these manuscripts are not only coming from basic fields of research such as material fabrication [ 12 13 ], structural control [ 14 15 ], elucidation of physical phenomena [ 16 17 ], and basic bio-related sciences [ 18 19 ], but also from applied fields such as catalysis [ 20 21 ], sensors [ 22 23 ], devices [ 24 25 ], environmental research [ 26 27 ], energy [ 28 29 ], and biomedical [ 30 31 ] fields. In this thematic issue entitled “Nanoarchitectonics for advanced applications in energy, environment and biology”, the authors also discuss coordination-assembled myricetin nanoarchitectonics [ 32 ], nanoarchitectonics for membranes with enhanced gas separation capabilities [ 33 ], nanoarchitectonics of the cathode of Li–O 2 batteries [ 34 ], nanoarchitectonics in moist-electric generation [ 35 ], nanoarchitectonics for drug delivery systems [ 36 ], nanoarchitectonics to entrap living cells [ 37 ], among other papers in which the concept of nanoarchitectonics has been applied to a variety of targets.…”
mentioning
confidence: 99%